2017
DOI: 10.1111/eea.12633
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in the activity of selected antioxidant enzymes and malondialdehyde level in worker honey bees

Abstract: The recent decline in managed honey bee populations, Apis mellifera L. (Hymenoptera: Apidae), has caused scientific, ecological, and economic concern. Research into the formation of reactive oxygen species (ROS), antioxidative defense mechanisms, and oxidative stress can contribute to our understanding of bee survival and conservation of this species. Activities of superoxide dismutase (SOD), catalase (CAT), and glutathione S‐transferase (GST) enzymes together with levels of malondialdehyde (MDA) were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 47 publications
3
16
0
3
Order By: Relevance
“…We presume that the cause of both increased parasite prevalence and stress in commercial colonies is the anthropogenic influence, that is, inadequate beekeeping practices [12]. This is in line with some previous findings that imbalanced food and different metabolic demands develop oxidative and energetic stress [23,[51][52][53][54]. Significantly higher GOX gene expression in commercially kept colonies than in those kept in trmka hives is an additional finding in the current research.…”
Section: Discussionsupporting
confidence: 90%
“…We presume that the cause of both increased parasite prevalence and stress in commercial colonies is the anthropogenic influence, that is, inadequate beekeeping practices [12]. This is in line with some previous findings that imbalanced food and different metabolic demands develop oxidative and energetic stress [23,[51][52][53][54]. Significantly higher GOX gene expression in commercially kept colonies than in those kept in trmka hives is an additional finding in the current research.…”
Section: Discussionsupporting
confidence: 90%
“…Korayem et al [ 49 ] research showed that the higher the seasonal activity of workers, the higher the SOD activity. According to Orčić et al [ 50 ], high radical production is associated with increased metabolic processes resulting from increased activity, i.e., the oxygen demand of tissues during the flight.…”
Section: Discussionmentioning
confidence: 99%
“…In honey bees, enzymes such as the antioxidant superoxide dismutase and glutathione S-transferase are known to have microbiocidal activity (Nikolenko et al 2011). The activity of these enzymes is influenced by environmental factors associated with different seasons, and in winter workers, their levels decrease (Korayem et al 2012;Orčić et al 2017). This may explain the larger proportion of spores that survived in autumn than in summer bees which could, consequently, increase the risk of infection of autumn or winter flowering crops such as almonds and canola.…”
Section: Discussionmentioning
confidence: 99%
“…Feeding experiments were conducted in mid-February and late March of 2018 using summer and autumn workers, respectively. These two types of workers were chosen because environmental factors related to season can influence the worker's metabolism due to changes in the levels of microbiocidal enzymes in the digestive tract (Orčić et al 2017), which could damage or digest fungal spores. For each experiment, newly emerged workers were obtained by placing brood frames with late stage pupae, originating from three hives, in an incubator in the dark at 34°C and approximately 50-70% relative humidity (Hatjina et al 2013).…”
Section: Preparation Of Beesmentioning
confidence: 99%